2018
DOI: 10.1016/j.afos.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of osteoporosis and osteopenia in an apparently healthy Indian population - a cross-sectional retrospective study

Abstract: ObjectivesAn understanding of bone mineral density (BMD) pattern in a population is crucial for prevention and diagnosis of osteoporosis and management of its complications in later life. This study aimed to screen the bone health status and factors associated with osteoporosis in an apparently healthy Indian population.MethodsA retrospective review of medical records was done in a tertiary-care hospital for the subjects who had undergone preventive health-check-ups that included BMD measurements at femur-neck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 56 publications
(60 reference statements)
3
34
0
3
Order By: Relevance
“…This study showed that as the age increases, the prevalence of osteoporosis increases. This finding is consistent with result of Hemmati et al [3], Tian and et al in China [9], and Kaushal et al in India [8].…”
Section: Logistic Regression Results Of the Reviewing Of Relationshsupporting
confidence: 93%
See 2 more Smart Citations
“…This study showed that as the age increases, the prevalence of osteoporosis increases. This finding is consistent with result of Hemmati et al [3], Tian and et al in China [9], and Kaushal et al in India [8].…”
Section: Logistic Regression Results Of the Reviewing Of Relationshsupporting
confidence: 93%
“…In a study by Kaushal and et al in 2017 in the healthy population of India, the overall prevalence of osteoporosis and osteopenia was 6.9% and 34%, respectively. The prevalence of osteoporosis in men and women in the lumbar spine was 11.1% and 3.9% respectively, and in the femoral neck were 4.1% and 3.6%, respectively [8]. Tian et al in a study in China reported a prevalence of osteoporosis in the distal region of forearm in women over 50 years old, 65.6% and in men older than 60 years old was 8.08% [9].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reasons attributed for lower bone mineral density (BMD) in Indians include possible genetic differences, nutritional deficiency and smaller skeletal size. 6 Osteoporosis-related fractures are associated with substantial pain, suffering, disability, and possibly even death for the affected patients. Further, increasing longevity has resulted in an increasing number of senior citizens globally; life expectancy at present is ~67 years in India and is expected to increase to 71 years by 2025 and to 77 years by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, increasing longevity and a greater proportion of the Indian population over the age of 50 years are likely to result in an increased number of people affected by osteoporosis. 6 It has clinical and public health implications because of the mortality, morbidity, and cost of medical care related with osteoporotic fracture. About 1.6 million hip fractures occur each year worldwide and the incidence is set to increase to 6.3 million by 2050.…”
Section: Introductionmentioning
confidence: 99%